2007
DOI: 10.1007/s11604-006-0112-4
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector CT findings suggesting a perforation site in the gastrointestinal tract: analysis in surgically confirmed 155 patients

Abstract: MDCT was valuable for identifying the presence and level of GI tract perforation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 25 publications
1
28
0
6
Order By: Relevance
“…Bu nedenle duvar devamsızlığının yanında perforasyonda görülen diğer bulgular ve bu bulguların görüldüğü yerler kullanılarak perforasyon yerinin belirlenmesi tedavi seçeneğine karar vermede yardımcıdır. [8][9][10] Bu çalışmada, künt travmaya veya travma dışı nedenlere bağlı gastrointestinal kanal perforasyonu olan hastalarda BT ile perforasyon bulgularını ve bu bulgular yardımı ile perforasyon yerinin belirlenmesinde BT'nin tanısal değerini araştırdık.…”
Section: Resultsunclassified
See 3 more Smart Citations
“…Bu nedenle duvar devamsızlığının yanında perforasyonda görülen diğer bulgular ve bu bulguların görüldüğü yerler kullanılarak perforasyon yerinin belirlenmesi tedavi seçeneğine karar vermede yardımcıdır. [8][9][10] Bu çalışmada, künt travmaya veya travma dışı nedenlere bağlı gastrointestinal kanal perforasyonu olan hastalarda BT ile perforasyon bulgularını ve bu bulgular yardımı ile perforasyon yerinin belirlenmesinde BT'nin tanısal değerini araştırdık.…”
Section: Resultsunclassified
“…Imuta ve arkadaşları [10] 8-slice multi-dedektör BT (MDBT) ile 155 hastada geriye dönük bir çalışma yapmıştır. Bu çalışmada kesit kalınlığı 2,5 mm olarak kullanılmıştır.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…47 Solis et al 38 showed in a small retrospective study that CT delays surgery in patients with pneumoperitoneum on abdominal radiograph. Thus, given the risk of unnecessary laparotomy and unnecessary delays in surgery where it is required, patients with strong clinical suspicion of GI perforation should ideally have a CT instead of Abdominal X-ray (AXR) as first line investigation (Figure 3).…”
Section: Gastrointestinal Perforationmentioning
confidence: 99%